Ranking effective risks on human resources threats in natural gas supply projects using ANP-COPRAS method: Case study of Shiraz. (April 2021) - Balali, Amirhossein; Valipour, Alireza; Edwards, Rodger; Moehler, Robert
Highlights: Existing risks in gas supply projects were identified. Risk assessment criteria for ranking risks were identified. Risk assessment criteria for ranking risks were weighed. Identified risks in gas supply projects were ranked. Abstract: Recently, there has been an increase in the number of accidents and risks in urban natural gas supply such as fire and explosion in cities. These risks and accidents have caused a lot of financial and life damages. Due to the high number of incidents in the world, identification and evaluation of these risks seems essential. This study aims to identify and evaluate the risks in urban natural gas projects in Shiraz. The research tools of this study were interviews, questionnaires and case studies' information.. In this research, the COPRAS (Complex Proportional Assessment) method was used to carry out risk assessment and ANP (Analytic Network Process) technique was used to obtain weights of each risk assessment criteria. 12 risk assessment criteria were identified, of which "Installation", "Risk of leakage" and "Risk impact" were identified as the three most important criteria. 32 risks were identified in natural gas supply projects in Shiraz of which "Municipal interventions", "Mistakes in repairing gas supply pipes" and "Financial inability of contractors to insulate tubes" were the most important. The results can help stakeholders in excavation projects to identify and manage risks.